The Impact of Job Embeddedness on Supporting the Corporate Reputation: A Field Study - El Ziadi, Basant (The Arab Journal of Administration, 2020)
The study aims to be acquainted with the impact of the dimensions of job embeddedness (represented in organizational fit, community fit, organizational sacrifice, community sacrifice, organizational links and community links) on supporting the corporate reputation. Also to be acquainted with the moral differences of job embeddedness and supporting the corporate reputation as for the employees according to demographic variance (Type of job – age – Experience). A study was made on the employees working at Ezz Steel Company (El Sadat City). The actual research sample is represented in (230) individuals. The researcher used the following descriptive statistical methods: The Internal Consistency. - Cronbach’s Alpha. Arithmetic Means, standard deviations and proportional importance. Also the following Inferential methods are used: Path analysis. - Simple-Regression Analysis. Multi-Regression Analysis. T-test, and Analysis one way ANOVA (F-test). The study showed that there is a positive moral impact of statistical function for the dimensions of job embeddedness as a whole on supporting the corporate reputation. The results showed that the most effective dimensions is: fit dimension (organizational and community). It is followed by links dimensions(organizational and community). It is followed by sacrifice dimension (organizational and community) The study resulted in that there are moral differences in job embeddedness and supporting the corporate reputation of employees working at Ezz Steel Company – (El Sadat City) according to demographic differences (age – experience). Meanwhile, there are no differences between employees’ responses according to type of job according to job embeddedness dimensions and supporting the corporate reputation.